Rock fragmentation size distribution control in blasting: a case study of blasting mining in Changjiu Shenshan limestone mine - Gao, Pengfei; Pan, Cheng; Zong, Qi; Dong, Chunliang (Frontiers in Materials, 2023)
Deep-hole bench blasting is the primary method for aggregate extraction in mines. However, factors such as complex geological conditions and suboptimal blasting parameters often result in uneven rock fragmentation and high fines content. This not only increases the cost and energy consumption of subsequent aggregate processing but also has adverse environmental implications. In this study, based on the Changjiu Shenshan limestone aggregate mining project in China, large-scale blasting experiments were conducted to investigate the influence of rock properties and blasting parameters on the size distribution of post-blast fragments and fines content. The results of the blasting experiments indicate that by controlling the size of the crushing zone and adjusting explosive performance, it is possible to significantly reduce fines content while improving mining efficiency. Recommended values for drilling and blasting parameters have been proposed based on geological conditions to more effectively control the generation of fines. The results highlight the importance of optimizing blasting parameters and charge structure for large-scale mining operations to achieve uniform rock fragmentation and low fines content. By adopting explosive performance adjustment methods based on reasonable control of the crushing zone, improving explosive performance can improve the economic benefits of mining operations, reduce energy consumption, and contribute to environmental protection.